No Gear? No Problem! Fitness Activities for Students With Limited Space and Equipment. Issue 6 (5th August 2021) - Wahl-Alexander, Zachary; Jacobs, Jenn M.; Kaeb, Barrett; Riley, Kenneth
Abstract: The U.S. Department of Health and Human Services recommends youth participate in at least one hour of moderate to vigorous physical activity each day to achieve various short- and long-term health benefits. Unfortunately, only two thirds of American-born children and adolescents meet these prescribed recommendations. The purpose of this article is to highlight various exercise techniques and innovative strategies physical education teachers can employ when facing limited physical space and equipment limitations.